Arsenic-induced responses in plants: Impacts on biochemical processes - Kumar S.; Rani V.; Singh S.; Kapoor D.; Dhanjal D.S.; Thakur A.; Pujari M.; Ramamurthy P.C.; Singh J. (My University, 2025)
Arsenic (As) overaccumulates into plants because of mineralization, mining activities, irrigation with contaminated groundwater, wood preservatives, herbicides, insecticides, and fertilization with solid municipal wastes. The state of arsenic (III) and (V) triggers an overproduction of reactive oxygen species like hydroxyl radical, oxide radical, and hydrogen peroxide, causing oxidative damage of various biochemicals like nucleic acids, proteins, and lipids. These ions also stimulate various enzymes like catalase, ascorbate peroxidase, glutathione reductase, superoxide dismutase, guaiacol peroxidase, and nonenzymatic components like glutathione, ascorbate, carotenoid, and A-tocopherol inside the plants and act as antioxidants. Therefore, the toxicity of arsenic is stated to negatively affect the productivity as well as the quality of plants and impact the well-being and health of animals and humans consuming it. With passing time, plants have started evolving and developing strategies to curb the toxic effect induced by arsenic via mechanisms like accumulation of compatible solutes (mannitol, glycine betaine, sugar, and proline), biosynthesis of polyphenols, compartmentalization, and metal-binding proteins. Moreover, exogenous application of nitric oxide (NO), phosphate, proline, and potassium has been reported to reduce arsenic toxicity substantially. In this chapter, we explored the effects of arsenic on biochemical processes, oxidative stress, carbohydrate metabolism, lipid metabolism, and protein metabolism in arsenic-induced plants. We also discussed some directions to uncover the precise molecular mechanism involved in ameliorating arsenic-induced toxicity responses in different plants. © 2023 John Wiley & Sons, Inc.